MUSEUM AS A HEALTH AND WELLBEING FACILITATOR IN PANDEMIC ERA: A PERSPECTIVE FROM MUSEUM COMMUNICATION - Ciwuk Musiana Yudhawasthi (Scriptura, 2022)
During the pandemic, museums in the world began to move to expand their role in social interaction. Referring to the proposed new museum definition from ICOM which is still being discussed, museums are expected to contribute to the health and well-being sector. Currently, all museums in the world are changing the way they work by using technology and carrying out all activities remotely by utilizing various applications to stay connected with their visitors. What about the condition of museums in Indonesia? how museums in Indonesia carry out their role as direct actors of social development beyond their educational role? Are museums in Indonesia more proactive in improving society lives with special consideration for marginalized groups, like a senior adult, disabled person, special need, people with dementia, schizophrenia, or people with mental health? How museums in Indonesia use technology to communicate with their users? Researchers use qualitative studies and virtual ethnographic methods to explore museums that use social media. The results of the study show that most of the museums in Indonesia are not aware of their role to contribute to the quality of urban life, especially during the pandemic. And museum communication skills in the pandemic era must be expanded through the use of the internet while still paying attention to the ethics and limitations that apply to each type of collection owned.